Prepaid Cards: Advantages, Disadvantages, and How to Choose - Selena Garrison (EDIS)
Prepaid cards are becoming popular, but are they a good choice for you? This 3-page fact sheet present the advantages and disadvantages of prepaid cards and then explain how to choose the best prepaid card, should you decide to use one. Written by Selena Garrison and published by the UF Department of Family, Youth and Community Sciences, February 2012.